TRENDS IN ECTOPIC PREGNANCY: A RETROSPECTIVE OBSERVATIONAL STUDY - AARTI SHARMA; DIVYANSHU CHOUDHARY; RAHIL KUMAR SHARMA; DILEEP DANDOTIYA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: An ectopic pregnancy occurs when fetal tissue implants outside the uterus or attaches to an abnormal/scarred portion of the uterus. If not diagnosed and managed promptly, it is associated with significant morbidity and mortality. The objective of the study is to determine the incidence of ectopic pregnancy and analyze its associated risk factors, clinical presentations, and management provided. Methods: A retrospective observational study of patients who were diagnosed with ectopic pregnancy and managed at ABVGMC, Vidisha, over a period of 1 year was done. Results: A total of 33 patients with ectopic pregnancy were included, with an incidence of 14.47/1000 deliveries. Out of them, 66.67% were multigravida, and 75.70% belonged to the 21–30 years age group. Of all risk factors, pelvic inflammatory disease (60.60%) was the most common, followed by the previous cesarean section (24.24%). The predominant symptom was amenorrhea (96.96%), followed by abdominal pain (75.75%) and bleeding per vaginum (69.69%). More than half of the patients presented with classical triads. On examination, adnexal fullness with tenderness and cervical motion tenderness were elicited in most. The most common type of ectopic pregnancy was ampullary tubal ectopic (96.96%). 57.57% of cases presented in a ruptured state. The mainstay of treatment was salpingectomy, and there was no mortality. Conclusion: The incidence of ectopic pregnancy is alarming in developing countries due to the high prevalence of pelvic inflammatory disease and cesarean section. Lack of early diagnosis and management led to ruptured ectopic, due to which conservative management was rendered impossible.